2012
DOI: 10.1007/s12550-012-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential oil from fresh leaves of Ocimum gratissimum L. on mycoflora during storage of peanuts in Benin

Abstract: The aim of this study was to evaluate the effect of essential oil from fresh leaves of Sweet Fennel (Ocimum gratissimum) on mycoflora and Aspergillus section Flavi populations in stored peanuts. Aspergillus, Fusarium and Mucor spp. were the most common genera identified from peanuts at post-harvest in Benin by using a taxonomic schemes primarily based on morphological characters of mycelium and conidia. The isolated fungi include Aspergillus niger, A. parasiticus, A. flavus, A. ochraceus, Fusarium graminearum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…The restrictions imposed by international food organism on the use of chemical synthesis preservatives due to health and environmental risks [7] increasingly encourage the use of essential oils in food preservation [8]. Essential oils as well as derived compounds possess a wide range of activities of which, the antimicrobial activity is most studied [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The restrictions imposed by international food organism on the use of chemical synthesis preservatives due to health and environmental risks [7] increasingly encourage the use of essential oils in food preservation [8]. Essential oils as well as derived compounds possess a wide range of activities of which, the antimicrobial activity is most studied [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…This result could be related to the capacity of organic solvent. Benini [16] and Adjou et al [17] showed that the concentration of essential oils extracted from species belonging to the Lamiaceae family were generally between 0.02 % and 1.31%. [4] .…”
Section: Physico-chemical Properties Of H Bracteosa Leaves Extractsmentioning
confidence: 99%
“…In another study by Kpoviesse et al (2014), they reported 32.96-35.43% of oxygenated monoterpenes in the EO of O. gratissimum cultivated in Benin, which is only half the quantity found in this study. Adjou et al (2012) identified 31 chemical compounds in the clove basil EO extracted from fresh leaves. The gas chromatography-mass spectrometry (GC-MS) analysis also indicated different groups of terpenes.…”
Section: Characteristics Of Growth Field and Clove Basil Essential Oilmentioning
confidence: 99%